Mobile based application for prediction of diabetes mellitus: FHIR Standard - Sharma, Meenakshi; Aggarwal, Himanshu (International Journal of Engineering and Technology, 2018)
Presently physicians providing clinical decision along clinical guidelines manually on basis of manual query toÂ  patients that involve documentation files of lab reports, medication description etc., that make practice sluggish and arduous. With development of mobile based application provide assistance to physician in providing quick decision in appropriate manner as patient data available any-time from any-where that will enhance quality of care in field of healthcare. HL7 standard promotes FHIR(Fast Health Interoperability Resource) standard and health information technology for mobile-health. Mobile health is not a vertical field, but a kind of horizontal field that has cut various impact of healthcare domains. This application provide the effective health management of patient's electronic health record with ease of user friendly interface, that can be accessed on role based authentication by numbers of actors like patient, physician, clinic staff and patient's family etc. Basically this study projected decision support system for prediction of chronic disease-Diabetic- Mellitus using FHIR(Fast Health Interoperability Resource) as standard for interoperability among hospital information system. Application provide physician's structured series of symptoms/signs as uploaded by patients, laboratory and staff. Series of questioner along with outcomes are formed, all outcomes appraised and tested by team of medical domain experts.Â